Carbon Nanodot–Based Fluorescent Method for Virus DNA Analysis with Isothermal Strand Displacement Amplification. (28th August 2019) - Yang, Dawei; Guo, Zhenzhen; Wang, Jing; Jin, Yakang; Mei, Qian; Miao, Peng
Abstract: In this work, a fluorescent method is developed for ultrasensitive detection of virus DNA, coupling DNA‐modified carbon nanodots (CDs) and an isothermal amplification technology. The sensitivity is significantly improved with cyclic strand displacement polymerization and highly luminescent CDs. Taking the hemagglutinin7 (H7) gene and neuraminidase 9 (N9) gene as examples, the limits of detection are 4.6 × 10 −15 and 3.4 × 10 −15 m, respectively. Furthermore, the proposed method is highly selective and capable of detecting target sequences in biological samples, indicating great potential for applications in life science research and clinical diagnosis. Abstract : DNA‐modified carbon nanodots are coupled with strand displacement amplification for sensitive detection of virus DNA. This method shows a limit of detection for H7 and N9 genes as low as femtomolar level. Furthermore, it is highly selective and capable of detecting target sequences in biological samples, which indicates promising applications in life science research and for clinical diagnosis.